A Survey of Attitudes & Perceptions of People with Disabilities. - Guyant, Andrea (My University, 2009)
This descriptive pilot study sought to gather insight into people's attitudes and perceptions of people with disabilities. The study was conducted via on online survey entitled People with Disabilities. The target population included students, alumni, classified staff member and faculty/academic staff members associated with the University of Wisconsin--Eau Claire.
Color poster with text, tables, and graphs (Spring 2009)
Keywords: People with disabilities--Public opinion; University of Wisconsin--Eau Claire--Faculty--Attitudes; University of Wisconsin--Eau Claire--Students--Attitudes; University of Wisconsin--Eau Claire--Employees--Attitudes; Posters